Isolation, Characterization, Proliferation and Differentiation of Synovial Membrane-derived Mesenchymal Stem Cells (SM-MSCs) from Osteoarthritis Patients - Marlina Marlina; Rizki Rahmadian; Armenia Armenia; Wahyu Widowati; Rizal Rizal; Hanna Sari Widya Kusuma; Satrio Haryo Benowo Wibowo; Wahyu Setia Widodo; Ika Adhani Sholihah (Molecular and Cellular Biomedical Sciences, 2020)
Background: Mesenchymal stem cells (MSCs) are the cells which have high renewal capacity and and are capable for differentiating into some types of cells. MSCs can be obtained from several tissues including bone marrow, synovial membrane, blood, adipose tissue and periosteum. The proliferation and self-repair ability of MSCs are the advantages to use as stem cells-based therapy of various diseases. The aim of this study was to determine the differentiation, characterization and proliferation of synovial membrane-derived MSCs (SM-MSCs).Materials and Methods: The cells proliferation capacity was determined by cell counting using trypan blue, characterization of MSCs (cluster of differentiation (CD)90, CD11b, CD73, CD34, CD19, CD45, CD105 and human leukocyte antigen-DR isotype (HLA-DR)) using flow cytometry analysis, and differentiation capability into three lineage cells was determined with red alcian blue, oil red O and alizarin staining.Results: The type culture of SM-MSCs was adherent and showed positive CD44, CD105, CD73, CD90 and negative of CD19, HLA-DR, CD11b, CD45, CD34 surface marker. Based on the result, SM-MSCs P3 showed differentiation potency into adipogenic, chondrogenic, and osteogenic lineage cells. The population doubling time of SM-MSCs has increased from P3 to P8. The population doubling time of SM-MSCs P3 was 1.69 days and SM-MSCs P8 was 3.64 days.Conclusion: The results indicated that SM-MCSCs from osteoarthritis patients are able to differentiate into osteocytes, chondrocytes, adipocytes and highly express of CD105, CD73, CD90, CD44 and negative for CD34, CD45, CD14, CD19.Keywords: synovial membrane, mesenchymal stromal cells, adipocyte, chondrocyte, osteocyte